Students’ Critical Thinking in Solving Mathematics Problems Based on Field-Independent and Field-Dependent Cognitive Styles - Roisatun Nisa; Siti Khabibah; Dwi Juniati (Universitas Negeri Surabaya, 2026)
The purpose of this study was to describe the critical thinking process of students with Field-Independent (FI) and Field-Dependent (FD) cognitive styles when they solved the Two-Variable Linear Equation System (SPLDV) problem, which is based on the Polya step and the Facione critical thinking indicator. This research is qualitative descriptive. The instruments in this study are the GEFT Test, the SPLDV problem-solving test and the interview guidelines are the research instruments. The results of the study show that FI students are able to understand and analyze data independently and systematically, use logical inference to choose a solution strategy, and provide a thorough procedural explanation. They are also capable of self-verification, which shows strong self-control In contrast, FD students face difficulties in selecting important information, making preparations that rely on the teacher's example, and performing inconsistent completion steps. Since the evaluation stage of FD students still depends on external justification, they also show a lack of self-regulation. These results confirm that cognitive style affects the activation of critical thinking indicators at each stage of problem-solving. In addition, cognitive style also provides implications for the importance of adaptive learning based on students' cognitive characteristics.